Antioxidant activities and chemical composition of hot water-soluble extracts and fractions of selected Schizophyllum commune Fr. strains / Alyaa Salah Rashid Al-Salihi - Alyaa Salah Rashid , Al-Salihi (2021)

(untitled)
Oxidative stress is a conjoint pathological mechanism that can be triggered by free radicals leading to cellular senescence or apoptosis. Antioxidants have the potential to inhibit free radicals’ generation and balance the irregulated oxidative stress to restore cellular homeostasis. Schizophyllum commune, also known as the split-gill mushroom, is well-known for its nutritional values and bioactive compounds. This study aimed to investigate the antioxidant activity and chemical composition of the hot water extracts of selected strains of S. commune including natural, gamma-irradiated and hybrid strains. The fruiting bodies of different strains of S. commune were subjected to hot water extraction and the extracts were evaluated by radical scavenging, and reducing capacity assays. Results showed that, overall, the antioxidant activity of the various strains was comparable. The natural strain W and the strain obtained when strain W was subjected to gamma-irradiation at a dose of 4000 Gy (W4000) consistently exhibited high antioxidant activities in all assays and they were either comparable or higher than common edible mushrooms, Pleurotus pulmonarius and Agaricus bisporus. Moreover, the gamma-irradiated strains R2000 and R4000 exhibited higher reducing activities (0.40 and 0.41 mmol Fe2+/g extract) than the parental strain R (0.27 mmol Fe2+/g extract). Furthermore, the hybrid strains WR and RW showed higher scavenging activities towards 2,2 diphenyl-1-picylhydrazyl radicals (1.40 and 1.45 mmol TE/g extract) than the parental strain R (1.17 mmol TE/g extracts), but lower than the parental strain W (1.78 mmol TE/g extract). There is a strong correlation between the antioxidant activity of the extracts and the levels of flavonoid and phenolic compounds (p < 0.01). In order to determine the nature of antioxidative components in the hot water extracts of S. commune, the extracts of strains W and W4000, were fractionated to yield fractions with distinct chemical components. Results indicated that the phenolics- and flavonoids-rich ethyl acetate and ethanol fractions exhibited higher scavenging activities towards DPPH radicals, and ferric reducing activities compared to the fractions containing mostly water-soluble components. Similar trends were observed for both W and W4000 strains. Our findings suggest that the observed antioxidant activities of the hot water extracts of S. commune is mainly attributed to the water-soluble, low- molecular-weight compounds rather than the water-soluble components such as polysaccharides and proteins which make up the bulk of the water extracts.